PEMBERDAYAAN GURU MADRASAH IBTIDAIYAH MELALUI TRANSFORMASI MANAJEMEN MUTU SUMBER DAYA MANUSIA (SDM) GUNA MENINGKATKAN MUTU MADRASAH SE KECAMATAN DIWEK KABUPATEN JOMBANG - Dr. Hj. Mardiyah, M.Ag; Qamariyah, M..PdI, Lailatul; Aminuddin Aziz, M.PdI, Abdullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2016)
The success of education at the school is largely determined by success in managingthe head of the educational staff in schools/madrasah. Principals have responsibilityfor improving the quality of teachers in achieving its objectives in addition to thegovernment's obligations. Implementation of management education personnel(teachers and staff) in Indonesia according Mulyasa, at least include; workforce planning, procurement personnel, dismissal of personnel, coaching and development, promotion and assessment. Activities meant to show that the provision of teachers aseducators very great concern in efforts to achieve the quality of the success of learners.Quality Management aims to develop human resources empowerment of teachers whoare expected to engage actively pushing to improve the quality of schools/madrasah.This devotion performed on MI Urwatul Wusqo PP. Al-Urwatul Wutsqo Bulurejo, MIPerguruan Muallimat in PP Walisongo Cukir, MI Tarbiyatul Aulad Bandung inGebang Malang Bandung and MI Ar-Rohman Nglaban Bendet. Relative activity ofteacher empowerment through developing quality human resources managementmodel in order to improve the quality of madrasah in Sub district Diwek Jombang, canbe summarized as follows: 1. In the beginning, the madrasah four management modelsare clerical, after empowering the community service program, the fourth madrasahmanagement models to increase to managerial model. 2. Subject devotion capable ofimplementing the quality management model of human resources fitted to thecharacteristics of each institution. 3. The quality of human resources managementmodel developed by Principals effective enough to increase the empowerment ofteachers in the fourth MI. 4. The research subjects were able to understand the qualityof human resources management capabilities and strength of institutions in improvingteacher quality through the transformation of the quality management of humanresources. 5. The research subjects understand their duties and functions as teachers(institution Asset, facilitator, motivator, mediator, and creator) in the teaching andlearning process.